2014
DOI: 10.1002/ange.201409248
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Steric Effects in the Development of a Palladium‐Catalyzed Alkyne Carbohalogenation: Stereodivergent Synthesis of Vinyl Halides

Abstract: We report our finding that by exploiting the synergistic steric effects between substrate and catalyst, an intramolecular Pd-catalyzed alkyne carbohalogenation can be achieved. This operationally simple method uses the bulky Pd/ Q-Phos combination and allows access to tetrasubstituted vinyl halides from the corresponding aryl chlorides, bromides, and iodides. Steric effects in the substrate play a key role by promoting C sp 2-halogen reductive elimination and enabling catalytic turnover. Through a reversible o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 31 publications
0
6
1
3
Order By: Relevance
“…In contrast to recent suggestions [21] we were not able to find am etallocarbene species as local minimum, neither with nor without the help of an external nucleophile.A ttempts to localize and isomerize such ac omplex led to huge energy barriers.H owever,a fter removing one PMe 3 from the metal complex generating the 14 VE Pd species syn-19,atransition state for the cis-trans isomerization 21.5 kcal mol À1 higher in energy than the starting complex could easily be localized (Figure 1). However,i ts structure did not resemble ac ommon carbene complex.…”
contrasting
confidence: 99%
“…In contrast to recent suggestions [21] we were not able to find am etallocarbene species as local minimum, neither with nor without the help of an external nucleophile.A ttempts to localize and isomerize such ac omplex led to huge energy barriers.H owever,a fter removing one PMe 3 from the metal complex generating the 14 VE Pd species syn-19,atransition state for the cis-trans isomerization 21.5 kcal mol À1 higher in energy than the starting complex could easily be localized (Figure 1). However,i ts structure did not resemble ac ommon carbene complex.…”
contrasting
confidence: 99%
“…[15] Nachfolgende Berichte der Gruppen von Buchwald, Sanford und weiteren haben das Spektrum Pd 0 /Pd II -katalysierter Methoden zur Installation von Kohlenstoff-Halogen-Bindungen erweitert. [6,16] Unter den aromatischen Halogeniden nehmen Aryliodide eine privilegierte Rolle ein, da sie einzigartige Eigenschaften aufweisen, wie eine überlegene Reaktivitätb ei Kreuzkupplungsreaktionen [17] oder ihre Anwendung in der hypervalenten Iodchemie. [18] Tr otz der jüngsten Fortschritte bei der übergangsmetallkatalysiertenI nstallation von Kohlenstoff-Halogen-Bindungen [6,11a,b,f, 12c,d] sind allgemeine und milde Methoden zur Installation von C(sp 2 )-Iod-Bindungen nach wie vor sehr gefragt.…”
unclassified
“…[6,7] With olefins, alkynylation to give 1,3-enynes has been limited to electronically activated substrates, in particular enones and acrylamides (Scheme 2 A). [7c, 8] By contrast, the selective C À H alkynylation reaction of unactivated alkenes has enjoyed considerably less attention, presumably because of the significant chemical challenges imposed by the additional reactivity pathways accessible to olefins, such as olefin E/Z isomerization, [3,[9][10][11][12][13] allylic functionalization, [14] and intramolecular nucleopalladation. [15,16] As part of a study focused on arenes, the groups of Zhao and Sarpong independently reported the reaction of three derivatives of two simple ethanamines, namely but-3-en-1-amine and cyclohexenylethanamine (Scheme 2 A).…”
mentioning
confidence: 99%